The Austerity Chic Interior, Gen Z, and Millennials' Domestic Dream - Magana, Urtzi Grau; Fernández-Abascal, Guillermo (Interiority, 2022)
This paper reviews domestic spaces completed in the last ten years to address the following research questions: How do Australian Gen Z and millennials in Sydney, who are currently shaping their future life, imagine their home? What are the domestic values and hopes of two generations that had their coming of age in the Information Era, and who naturally embrace digital technology and social media? What do size, scale, material, and technical innovation mean for a climate-conscious group of people that have lived through COVID-19 confinement, an endless real estate bubble, and recurrent economic crises? Grouped in five categories—sharing life, managing climate, naturalised interiors, reusing new materials, and austerity chic—the analysis of the study cases outlines these generations' emerging architectural interests. The five categories also inform a proposal for an interior constructed with fragments of the study cases that illustrates the paper’s conclusions and imagines a possible domestic space for Gen Z and millennials